Learning Strategies Used by Good EFL Adult Learners: a Case Study on University Students in Pare-Pare - Buyung Renaldy Adisaputra; Haryanto Atmowardoyo; Kisman Salija (ELT Worldwide: Journal of English Language Teaching, 2018)
This research aimed to find out the good EFL adult learners learning strategies in acquiring the foreign language and how the learning strategies affect the leaners achievement at Universitas Muhammadiyah Parepare. The method used in this research was qualitative method. The instrument were an interview and audio recorder. The participant of the research were the graduate students of Universitas Muhammadiyah Parepare within the age of 25-65 as one of the criteria of adult learners. The result of the research showed that the learning strategies applied by the learner were direct and indirect strategy. Direct strategy covered memory related strategy, cognitive strategy and compensatory strategy while metacognitive strategy, affective strategy and social strategy were included in indirect strategy.